Alterations in type 2 dopamine receptors across neuropsychiatric conditions: A large-scale PET cohort - Malén, T. (Elsevier, 2025)
Purpose: Aberrant dopaminergic function is linked with motor, psychotic, and affective symptoms, but studies have typically compared a single patient group with healthy controls.
Methods: Here, we investigated the variation in striatal (caudate nucleus, nucleus accumbens, and putamen) and thalamic type 2 dopamine receptor (D2R) availability using [11C]raclopride positron emission tomography (PET) data from a large sample of 437 humans including healthy controls, and subjects with Parkinson's disease (PD), antipsychotic-naïve schizophrenia, severe violent behavior, pathological gambling, depression, and overweight. We analyzed regional group differences in D2R availability. We also analyzed the interregional correlation in D2R availability within each group.
Results: Subjects with PD showed the clearest decline in D2R availability. Overall, the groups showed high interregional correlation in D2R availability, while this pattern was weaker in violent offenders. Subjects with schizophrenia, pathological gambling, depression, or overweight did not show clear changes in either the regional receptor availability or the interregional correlation.
Conclusion: We conclude that the dopaminergic changes in neuropsychiatric conditions might not only affect the overall receptor availability but also how coupled regions are across people. The region-specific receptor availability more profoundly links to the motor symptoms, while the between-region coupling might be disrupted in violence.